On some "minimal" Leibniz algebras - Kurdachenko, L.A.; Subbotin, I.Ya.; Chupordia, V.A. (Reports of the National Academy of Sciences of Ukraine, 2016)
The description of the Leibniz algebras, whose proper subalgebras are Lie algebras, and the Leibniz algebras, whose proper subalgebras are Abelian, is obtained.